Wingspan Stents for the Treatment of Symptomatic Atherosclerotic Stenosis in Small Intracranial Vessels: Safety and Efficacy Evaluation - Zhang, L.; Huang, Q.; Zhang, Y.; Liu, J.; Hong, B.; Xu, Y.; Zhao, W. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Until now, endovascular treatment of symptomatic atherosclerotic stenosis in small intracranial arteries (≤2.5 mm) was limited. We evaluated the safety and efficacy of the treatment by using Wingspan stents in arteries of this caliber. MATERIALS AND METHODS: From March 2007 to July 2010, 53 symptomatic intracranial stenoses with narrowing of at least 50% in 53 patients were treated by using Wingspan stents. Clinical manifestations and imaging features were recorded. RESULTS: The technical success rate was 98.1%. There were no serious complications, with the exception of 1 patient who experienced a small cerebral hemorrhage caused by perforation of microwire. Thirty-nine patients (74%) were available for follow-up imaging with DSA. ISR was documented in 13 of these patients, including 2 patients with symptomatic ISR. The median length of the vascular lesions was 5.39 mm, and patients whose vascular lesions were longer than 5.39 mm had a much higher incidence of ISR than patients whose vascular lesions were shorter than 5.39 mm (53% versus 15%, respectively). The median ratio of the reference artery diameter to the stent diameter was 0.78, and patients whose ratio was smaller than 0.78 had a much higher incidence of ISR than patients whose ratio was larger than 0.78 (53% versus 15%, respectively). CONCLUSIONS: In our series, percutaneous transluminal angioplasty and stent placement of small intracranial arteries by using Wingspan stents was safe. The ISR rate was relatively high; most patients having ISR were asymptomatic. Further follow-up is needed to assess the long-term efficacy of this procedure. ACTactivated clotting timeISRin-stent restenosisLMAlocation, morphology, and accessPTASpercutaneous transluminal angioplasty and stentingWASIDWarfarin Aspirin Symptomatic Intracranial Disease